"Click" post-functionalization of a metal–organic framework for engineering active single-site heterogeneous Ru(iii) catalysts1. Issue 48 (18th June 2015) - Wu, Suntao; Chen, Liyu; Yin, Biaolin; Li, Yingwei
<x xml:space="preserve">Abstract</x> A terpyridyl NNN-chelator has been successfully incorporated into MIL-101(Cr) by using a click post-synthetic modification method, offering a useful platform for metalation to prepare highly active and stable single-site heterogeneous catalysts.